Hospital Management and Outcomes of Stroke in Indigenous Australians: Evidence from the 2009 Acute Care National Stroke Audit. Issue 3 (April 2013) - Kilkenny, Monique F.; Harris, Dawn M.; Ritchie, Elizabeth A.; Price, Chris; Cadilhac, Dominique A.
Background: Indigenous Australians have greater stroke mortality rates than non-Indigenous people (97% Indigenous Australians are aged <65 years). Quality of care in hospital is an important factor for avoiding death and disability. No national review of acute stroke care for Indigenous Australians is available. Aims: We aimed to compare adherence with clinical processes and outcomes among Indigenous and non-Indigenous patients with acute stroke admitted to hospital. Methods: Hospitals participating in the National Stroke Audit of acute services in 2009 that provided data for at least one Indigenous patient were included ( n = 33, 37%). Differences in death/dependency (modified Rankin Score 3–6) at discharge were determined using two-level multivariate analysis adjusting for hospital site and patient variables. A matched subgroup analysis in those aged 18 to 64 years was also undertaken. Results: Among 1162 eligible patients (60% male; 18–64 years n = 305), 7% were Indigenous (18–64 years: 18%). Indigenous patients had a greater prevalence of stroke risk factors, e.g. diabetes, more had intracerebral hemorrhages (25% vs. 16% non-Indigenous, P = 0·05), and were less likely be treated in a stroke unit and receive timely allied health assessments than non-Indigenous patients. Indigenous patients aged 18–64 years had a threefold odds of dying or being dependent at discharge (Adjusted odds ratio = 3·09, 95% confidence interval = 1·07–8·95). Conclusions: Australian Indigenous patients with stroke received a reduced quality of care in hospitals and experienced worse outcomes than non-Indigenous patients. Indigenous patients require the provision of evidence-based care to increase their opportunities for optimal health outcomes following stroke. Further research to explain the differences is needed.